Establishing and Utilizing Strategic Partnerships for Vaccine-Preventable Diseases: Best Practices in Haiti. Issue 5 (September 2018) - Adrien, Paul; Francois, Jeannot; Parke, Dana M.; Bebekoski, Thomas; Boncy, Paul Jacques; Corvil, Salomon; Existe, Alexandre; Jacques, Roody; Joseph, Gerard; Kaljee, Linda M.; Kilgore, Paul E.; Christophe, Millien; et al.
Abstract : Abstract: On March 10 to 11, 2016, the Ministère de la Santé Publique et de la Population (Ministry of Health of Haiti) and the Global Health Initiative at Henry Ford Health System hosted their Second Annual Scientific Conference entitled, "Best Practices for Establishing and Utilizing Partnerships for Vaccine-Preventable Diseases in Haiti, " at the National Laboratory in Port-au-Prince, Haiti. The conference brought together Ministry of Health officials, researchers, clinicians, academics, public health professionals, and other stakeholders to discuss vaccine programs and policies in Haiti. This forum provides a learning and discussion space to fuel strategies and public health research responding to priority areas identified by the Ministry of Health, and consequently, this forum serves as counsel for the Ministry of Health in its decision making on strategies to prevent and control infectious diseases in Haiti. The following article summarizes the presentations and conclusions of the March 2016 conference and covers a variety of important issues relating to vaccines and vaccine-preventable diseases in Haiti, including Haiti's Expanded Program on Immunization, surveillance, logistical and funding challenges, and community approaches, as well as case studies detailing introduction of the pentavalent, rotavirus, oral cholera, and human papillomavirus vaccines in Haiti. Most importantly, this article highlights a model for effective partnerships for vaccines, a model that can transcend response to specific diseases and apply to all global health partnerships. Abstract : This paper covers a variety of important issues relating to vaccines and vaccine-preventable diseases in Haiti, including Haiti's Expanded Program on Immunization, surveillance, logistical and funding challenges, and community approaches, as well as case studies detailing introduction of the pentavalent, rotavirus, oral cholera, and HPV vaccines in Haiti. Most important, this paper highlights a model for effective partnerships for vaccines, a model that can transcend response to specific diseases and apply to all global health partnerships.